Overcoming the Initial Illegitimacy of Ideas - Eicher, Stephan (Corporate Underground, 2022)
This chapter presents how bootleggers uncover their underground projects to their organizations and overcome the initial illegitimacy of their ideas. This study seems to be the first attempt to link bootlegging research with legitimacy research to explain this endeavor.We find that bootleggers just as other innovators need to win legitimacy for their projects. To overcome initial illegitimacy, we find that they follow several known but also several new patterns. Consequently, this chapter expands the knowledge on legitimacy seeking behavior of innovators and closes the research gap of how bootleggers successfully uncover their clandestine projects. Our collection of cases furthermore highlights that managers should listen carefully when being confronted with such projects. Innovations that may appear illegitimate at first can turn into important assets for their firms.
CRIS-Team Scopus Importer:2024-12-16

Uncovering Covert Innovation - Eicher, Stephan (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
It is of central importance for companies to be innovative. To maximize their innovation potential, companies often rely on formal systems and processes for innovation management. It has been shown that such attempts have the side effect of inhibiting a number of valuable innovations. Some employees proceed informally and smuggle their innovations past formal barriers. Stephan Eicher analyses the interaction between bootleggers and their management. Using both qualitative and quantitative methods, he answers three primary research questions. What is the current state of research on bootlegging in R&D? How do bootleggers overcome illegitimacy upon disclosing their covert projects to decision-makers? How do different management styles and approaches affect the incidence of bootlegging? The results of this research paint a vivid picture of the relationship between covert innovation projects and the official management world of companies. <br
Keywords: Uncovering Covert Innovation; Bootlegging; Illegitimacy; Management’s Attitude; Creative Deviance; Legitimacy; Entrepreneurship; Innovation; R&D; New Product Development; Underground innovation projects